Out here an anthology of Takatāpui and LGBTQIA+ writers from Aotearoa - Tse, Chris 1982-; Barnes, Emma (Auckland University Press, 2021)
This is an anthology of queer New Zealand voices. We became teenagers in the nineties when New Zealand felt a lot less cool about queerness and gender felt much more rigid. We knew instinctively that hiding was the safest strategy. But how to find your community if you're hidden? Aotearoa is a land of extraordinary queer writers, many of whom have contributed to our rich literary history. But you wouldn't know it. Decades of erasure and homophobia have rendered some of our most powerful writing invisible. Out Here will change that. This landmark book brings together and celebrates queer New Zealand writers from across the gender and LGBTQIA+ spectrum with a generous selection of poetry, fiction, creative nonfiction, and much, much more. From established names to electrifying newcomers, the cacophony of voices brought together in Out Here sing out loud and proud, ensuring that future generations of queers are afforded the space to tell their stories and be themselves without fear of retribution or harm.
Includes poems, short stories, comics, plays and excerpts from larger works
[Poem] by Simone Brighton includes square brackets in the title
Keywords: Geschichte 2000-2021; LGBT; Englisch; Homosexualität; Lyrik; Literatur; Neuseeland; New Zealand literature / 21st century; Gay community / New Zealand / Literary collections; Lesbian community / New Zealand / Literary collections; Sexual minority community / New Zealand / Literary collections; Gay culture / New Zealand / Literary collections; Sexual minority culture / New Zealand / Literary collections; Littérature néo-zélandaise / 21e siècle; Communautés homosexuelles / Nouvelle-Zélande / Anthologies; Communautés lesbiennes / Nouvelle-Zélande / Anthologies; Culture homosexuelle / Nouvelle-Zélande / Anthologies; Gay community; Gay culture; Lesbian community; New Zealand literature; Sexual minority community; Sexual minority culture; New Zealand; Takatāpui; Tuhinga kōrero; 2000-2099; Poetry; poetry; short stories; Literary collections; Drama; Short stories; Théâtre; Poésie; Nouvelles; Anthologie